The downside of scarcity: Scarcity appeals can trigger consumer anger and brand switching intentions. Issue 8 (5th April 2021) - Biraglia, Alessandro; Usrey, Bryan; Ulqinaku, Aulona
Abstract: Brands often use scarcity appeals to promote sales. However, there is limited research investigating how consumers react when they are unable to obtain items that are advertised using scarcity appeals in terms of limited quantity. In two studies, experimental and correlational, we show that consumers who do not get the product associated to scarcity appeals (vs. not) have higher intentions to switch to competitor brands. This effect is mediated by consumer anger. We present theoretical contributions in research on scarcity appeals and consumer emotions (i.e., anger) and we discuss managerial implications of how scarcity appeals can sometimes backfire and lead to consumers switching to other competitor brands when they fail to obtain the product advertised as limited in quantity.